Thermodynamic properties for MMoO4 (M = Mg, Sr and Ba) as the end-members of the yellow phases formed in the nuclear fuel waste glasses. (November 2018) - Morishita, Masao; Kinoshita, Yoshiki; Nozaki, Ai; Yamamoto, Hiroaki
Abstract: The standard molar entropy Δ 0 T S m °, at 298.15 K of MgMoO4 (cr) of the end-members of the yellow phases formed in the nuclear fuel waste glasses was determined by measuring C p, m ° at the temperature of 2 K and above using the most recent Debye-Einstein formula. The Δ 0 T S m ° data obtained in our previous study for SrMoO4 (cr) and BaMoO4 (cr) were re-evaluated using this most recent formula. The standard Gibbs free energies of formation, Δ f G m °, of MgMoO4, SrMoO4 (cr) and BaMoO4 (cr) were determined by combining the Δ 0 T S m ° data with the reference data for the standard enthalpy of formation, Δ f H m ° . The Δ f G m ° of MoO4 2− (aq) was updated from the thermodynamic cycle based on the data obtained in the present work. The unknown standard Gibbs free energy of solution, Δ sln G m °, and the solubility product, K s, at 298.15 K for MgMoO4 were predicted. The thermodynamic values were obtained as follows: Δ 0 T S m ° (MgMoO4 (cr), 298.15 K)/(J K −1 mol −1 ) = 119.11 ± 1.19; Δ 0 T S m ° (SrMoO4 (cr), 298.15 K)/(J K −1 mol −1 ) = 136.44 ± 1.36; Δ 0 T S m ° (BaMoO4 (cr), 298.15 K)/(J K −1 mol −1 ) = 152.61 ± 1.53; Δ f G m ° (MgMoO4 (cr), 298.15 K)/(kJ mol −1 ) = −1295.73 ± 0.91; Δ f G m ° (SrMoO4 (cr), 298.15 K)/(kJ mol −1 ) = −1441.32 ± 1.36; Δ f G m ° (BaMoO4 (cr), 298.15 K)/(kJ mol −1 ) = −1443.29 ± 1.33; Δ f G m ° (MoO4 2− (aq), 298.15 K)/(kJ mol −1 ) = −836.63 ± 0.97. Δ sln G m ° (MgMoO4 (aq), 298.15 K)/(kJ (mol of MoO4 2− (aq)) −1 ) = 3.72 ± 1.88. K s (MgMoO4 (aq), 298.15) = 2.23 × 10 −1 ± 4.46 × 10 −2 The thermodynamic data obtained in this work are expected to be useful for nuclear fuel waste safety management. Graphical abstract: Highlights: The thermodynamic properties for the molybdates formed in the nuclear fuel waste glasses were investigated. C p, m ° of MgMoO4 was measured followed by determining Δ 0 T S m ° and Δ f G m ° via the recent developed Debye Einstein formula. Δ 0 T S m ° and Δ f G m ° of SrMoO4 and BaMoO4 obtained in our previous study were re-evaluated as in the same way of MgMoO4 . Δ f G m ° of MoO4 2- was updated from the thermodynamic cycle on the basis of the present obtained data. The present obtained thermodynamic data are expected be useful for the nuclear fuel waste safety management.